Utilização de zinco aspergido termicamente como anodo de sacrifício para a proteção interna de juntas soldadas - Gervásio, João Paulo Klausing (2018)
The corrosive fluids transportation through carbon steel pipelines may be critical due to internal corrosion. To avoid failures, internal coatings may be applied in order to insulate the inner metal wall of the pipe. However, when the tubes are welded together, the heat generated during the welding process damages the inner coating. As a result, the ends of the tubes are uncoated and subjected to corrosion. There are solutions to this problem, but all have some kind of inconvenience, either by the cost of implementation or by the difficulty of application. This work aims to present the results of the application tests of an alternative method: zinc thermally sprayed as sacrificial anode for internal protection of welded joints. Electrochemical, immersion and characterization tests were used to prove that this zinc coating can work as an anode and eventually replace it.